2014
DOI: 10.1115/1.4026959
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Ice-Sloping Structure Interactions With the Cohesive Element Method

Abstract: S u sta ina b le A rc tic M a rin e and C oastal T e c h n o lo g y (S A M C oT ), C entre fo r R esearch-Based In n o vatio n (CRI), Hillerborg et al. in Ref. [20] examined the available fracture mechanics theories (stress intensity factor, energy balance approach, and Dugdale and Barrenblatt approaches) to describe crack initiation and propagation in concrete (quasi-brittle mate rial) by means of the finite element approach. Then, they proposed the fictitious crack model (also called cohesive crack model or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…The mesh size influences both the maximum load and the load frequency greatly. This finding is similar to those in Wang et al and Lu et al for simulating ice-sloping structure interactions [17,18]. It is also found that the mean, standard deviation, and maximum values derived from the simulated ice forces increase with increasing failure strain.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The mesh size influences both the maximum load and the load frequency greatly. This finding is similar to those in Wang et al and Lu et al for simulating ice-sloping structure interactions [17,18]. It is also found that the mean, standard deviation, and maximum values derived from the simulated ice forces increase with increasing failure strain.…”
Section: Discussionsupporting
confidence: 90%
“…The simulated crushing forces agreed well with the experimental results. Lu et al and Wang et al carried out numerical simulations of interactions between level ice and sloping structure using the cohesive element method [17,18]. Zhou et al proposed a numerical model to simulate the non-simultaneous crushing force acting on the cylindrical structures of wind turbines [19].…”
Section: Introductionmentioning
confidence: 99%
“…CZM was applied to analyzing the behavior of ice by Mulmule and Dempsey [17,18]. Afterwards, some other researchers [19][20][21][22][23] applied CEM to simulate the interactions between level ice and marine structures.…”
Section: Cohesive Element Methodsmentioning
confidence: 99%
“…CZM was firstly proposed by Hillerborg et al [21] to model the local crack propagation of an unreinforced concrete beam. Due to the good performance of CEM in modeling the initiation and propagation of crack, many researchers have introduced CEM into ice mechanics to simulate the fracture of ice material [22,23,24,25].…”
Section: Numerical Modelsmentioning
confidence: 99%